Clinical Intervention Using Focused Ultrasound (FUS) Stimulation of the Brain in Diverse Neurological Disorders - Baek, Hongchae; Lockwood, Daniel; Mason, Emily Jo; Obusez, Emmanuel; Poturalski, Matthew; Rammo, Richard; Nagel, Sean J.; Jones, Stephen E. (Frontiers in Neurology, 2022)
Various surgical techniques and pharmaceutical treatments have been developed to improve the current technologies of treating brain diseases. Focused ultrasound (FUS) is a new brain stimulation modality that can exert a therapeutic effect on diseased brain cells, with this effect ranging from permanent ablation of the pathological neural circuit to transient excitatory/inhibitory modulation of the neural activity depending on the acoustic energy of choice. With the development of intraoperative imaging technology, FUS has become a clinically available noninvasive neurosurgical option with visual feedback. Over the past 10 years, FUS has shown enormous potential. It can deliver acoustic energy through the physical barrier of the brain and eliminate abnormal brain cells to treat patients with Parkinson's disease and essential tremor. In addition, FUS can help introduce potentially beneficial therapeutics at the exact brain region where they need to be, bypassing the brain's function barrier, which can be applied for a wide range of central nervous system disorders. In this review, we introduce the current FDA-approved clinical applications of FUS, ranging from thermal ablation to blood barrier opening, as well as the emerging applications of FUS in the context of pain control, epilepsy, and neuromodulation. We also discuss the expansion of future applications and challenges. Broadening FUS technologies requires a deep understanding of the effect of ultrasound when targeting various brain structures in diverse disease conditions in the context of skull interface, anatomical structure inside the brain, and pathology.